Hi all. I have been trying to understand propagation of error of exponents. Most an. Chem textbooks I see say y = a^x, sy/y = (sa/a)*x. But say y = a*b, then sy/y = ((sa/a)^2 + (sb/b)^2)^.5 . if a = b then sy/y= (2*(sa/a)^2)^.5 = 2^.5*abs(sa/a). This shows the rule y=a^x, sy/y= x^.5*abs(sa/a).(adsbygoogle = window.adsbygoogle || []).push({});

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Propagation of error: exponents

**Physics Forums | Science Articles, Homework Help, Discussion**